International Trade and Spatial Competition - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
The consequences of free trade in an international spatial duopoly are investigated, under different market regimes. The optimal setting for both countries appears to be a private duopoly in which both firms operate under the same fiscal regime and a side payment from the larger to the smaller country occurs.
Keywords: 330